Translating the realities of cult: the case of the Book of the Temple - Quack, Joachim Friedrich (Greco-Egyptian interactions, 2016)
This chapter is concerned with the ‘Book of the Temple’, a recently identified priestly manual concerned with ritual procedures, originally composed in classical Egyptian, but later translated into Demotic and Greek. It concentrates on two surviving Greek fragments, which are shown to come from the same papyrus originating in the town of Oxyrhynchus in the 2nd century CE. The chapter also discusses the cultural affiliation of Oxyrhynchus, which is sometimes believed on the basis of the large numbers of Greek papyri surviving from there to have been predominantly Greek, but on closer examination turns out to preserve elements of still thriving Egyptian traditions.
Gesehen am 01.06.2017
Keywords: Konferenzschrift